2008
DOI: 10.1007/s10646-008-0292-z
|View full text |Cite
|
Sign up to set email alerts
|

A biotic ligand model-based toxicodynamic approach to predict arsenic toxicity to tilapia gills in cultural ponds

Abstract: Farming of tilapia Oreochromis mossambicus is an important aquacultural activity in Taiwan. Due to the elevated arsenic (As) concentration in pond water, it is important to assess the bioavailability and toxicity of As to tilapia for protection of aquatic life and human health. In the present study, we developed a biotic ligand model (BLM)-based toxicodynamic approach to dynamically predict both acute and chronic effective concentrations of As to tilapia in two tilapia farms located at Pudai and Chiangchun cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…According to this assumption, some models were developed based on the common BLM to predict the time course of toxicity of metals with fixed binding constants. These separate studies found that the fraction of binding sites occupied by the metal causing 50% effect (f 50 ) decreased with exposure time (Chen et al, 2009;Chen and Liao, 2010). Binding constants of Ca, Mg and Na obtained for Daphnia magna in a chronic (21 d) Zn-BLM were 0.2-0.4 log units lower than in an acute (48 h) Zn-BLM (Heijerick et al, 2002(Heijerick et al, , 2005.…”
Section: Introductionmentioning
confidence: 97%
“…According to this assumption, some models were developed based on the common BLM to predict the time course of toxicity of metals with fixed binding constants. These separate studies found that the fraction of binding sites occupied by the metal causing 50% effect (f 50 ) decreased with exposure time (Chen et al, 2009;Chen and Liao, 2010). Binding constants of Ca, Mg and Na obtained for Daphnia magna in a chronic (21 d) Zn-BLM were 0.2-0.4 log units lower than in an acute (48 h) Zn-BLM (Heijerick et al, 2002(Heijerick et al, , 2005.…”
Section: Introductionmentioning
confidence: 97%
“…Additional references (e.g., publications that only focus on the metalgill binding interaction) can be found in Ardestani et al (2014). Ag Bury et al, 2002;Janes and Playle, 1995;McGeer et al, 2000;Morgan and Wood, 2004;Paquin et al, 1999. As Chen et al, 2009.…”
Section: Metalmentioning
confidence: 99%